2021
DOI: 10.3390/f12020126
|View full text |Cite
|
Sign up to set email alerts
|

Variable-Exponent Taper Equation Based on Multilevel Nonlinear Mixed Effect for Chinese Fir in China

Abstract: A variable-exponent taper equation was developed for Chinese fir (Cunninghamia lanceolate (Lamb.) Hook.) trees grown in southern China. Thirty taper equations from different groups of models (single, segmented, or variable-exponent taper equation) were compared to find the excellent basic model with S-plus software. The lowest Akaike information criteria (AIC), Bayesian information criteria (BIC), and -2loglikelihood (-2LL) was chosen to determine the best combination of random parameters. Single taper models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…SpeedTree is currently a more professional and complete tree 3D modeling software [31]. The trunk of the Chinese fir is straight; therefore, the Chinese fir shaving equation could be taken for the 3D model of the trunk as the outer contour constraint [32][33][34]. Then, the skeleton of the 3D trunk model was constructed in the speed tree, and the Chinese fir bark texture map was added.…”
Section: Constructing Coupling Model Of 3d Chinese Fir Trunk Branches...mentioning
confidence: 99%
“…SpeedTree is currently a more professional and complete tree 3D modeling software [31]. The trunk of the Chinese fir is straight; therefore, the Chinese fir shaving equation could be taken for the 3D model of the trunk as the outer contour constraint [32][33][34]. Then, the skeleton of the 3D trunk model was constructed in the speed tree, and the Chinese fir bark texture map was added.…”
Section: Constructing Coupling Model Of 3d Chinese Fir Trunk Branches...mentioning
confidence: 99%
“…The mixed model consists of fixed parameters and random parameters, and the random parameters are added to the fixed parameters of the nonlinear model, which vary with changes in different blocks. Zhang et al (2021) established the variableexponent taper equation for Chinese fir and found that the nonlinear mixed effect model based on the tree-level effect performed the best. Therefore, in this study, a nonlinear mixed effect model was developed according to tree-level effects.…”
Section: Nonlinear Mixed Effect Modelmentioning
confidence: 99%
“…Therefore, in this study, different random parameters were combined separately. The optimal combination of fixed and random parameters was determined by comparing the minimum values of the statistics: Akaike's information criterion (AIC), Bayesian information criterion (BIC) and twice the negative log-likelihood (−2LL; Scolforo et al, 2019;Liu et al, 2020;Zhang et al, 2021), their expressions are provided at later section (equations 12~15).…”
Section: Nonlinear Mixed Effect Modelmentioning
confidence: 99%
See 2 more Smart Citations